Physical and biological engineering of polymer scaffolds to potentiate repair of spinal cord injury. (March 2021) - Luo, Yiqian; Xue, Fei; Liu, Kai; Li, Baoqin; Fu, Changfeng; Ding, Jianxun
Abstract: Although the mortality rates of patients suffering from spinal cord injury (SCI) have decreased as the modalities of clinical therapy have been improved, the recovery of motor and sensory functions remains a challenge, ultimately leading to paraplegia or quadriplegia. Recently, neural tissue engineering scaffolds with appropriate physical and biological functions have been extensively developed to promote nerve regeneration and improve motor and sensory functions during SCI therapy. In this work, we summarized the physical support and bioelectrical signal conduction of polymer scaffolds for SCI repair from the aspects of biocompatibility, biodegradation, internal structure, mechanical performance, and conductivity. In addition, the biological functions of the polymer scaffolds were reviewed for the reversal of adverse pathophysiological factors to improve the microenvironments of the injured site and promote endogenous neurogenesis during SCI therapy. Moreover, the future development of these engineered scaffolds for potential clinical applications was predicted. Graphical abstract: Unlabelled Image Highlights: Polymer scaffolds possess enormous potential in the repair of spinal cord injury. The optimized physical properties of scaffolds provide a favorable microenvironment for spinal cord injury repair. The biologically functionalized scaffolds reverse the adverse factors during spinal cord injury repair.